2008
DOI: 10.1159/000147171
|View full text |Cite
|
Sign up to set email alerts
|

Decidualization of Ovarian Endometriosis during Pregnancy Mimicking Malignancy: Report of Three Cases with a Literature Review

Abstract: Background: Intracystic papillary excrescence is a characteristic morphological feature of ovarian malignancy. A few recent reports have demonstrated that ovarian endometriotic cysts, undergoing decidualization during pregnancy, occasionally show excrescence, necessitating surgery during pregnancy; however, this phenomenon is not well recognized among clinicians. Cases: Three pregnant women with decidualized ovarian endometriosis showed excrescence. Both ultrasound and magnetic resonance imaging (MRI) preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…For this reason, an appropriate diagnosis is mandatory, but the differentiation of a mucinous from a nonmucinous cyst and, especially, the quantification of its malignant potential, are very difficult tasks because all imaging techniques, including MRI, have been inconsistent [14,15,16]. It is estimated that MRI only has an accuracy that varies between 20 and 80% [17].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, an appropriate diagnosis is mandatory, but the differentiation of a mucinous from a nonmucinous cyst and, especially, the quantification of its malignant potential, are very difficult tasks because all imaging techniques, including MRI, have been inconsistent [14,15,16]. It is estimated that MRI only has an accuracy that varies between 20 and 80% [17].…”
Section: Discussionmentioning
confidence: 99%
“…Each of our patients avoided the complication of surgery and obtained a spontaneous pregnancy that finally resulted in a positive effect on both symptomatology and endometriotic lesions. Previous authors have observed the sonographic characteristics of decidualized, hypervascularized endometriomas during pregnancy [22][23][24][25][26][27] but this is the first report on ultrasound pattern modification of DIE occurring during a spontaneous pregnancy.…”
Section: Commentmentioning
confidence: 99%
“…In the current literature, the presence of ovarian deciduosis is reported as a rare phenomenon [15,16]. With 10.1% of Cesarean sections presenting deciduosis, our findings suggest that macroscopic decidual lesions are more frequent than initially believed during pregnancy.…”
Section: Discussionmentioning
confidence: 48%